A review of human skin detection applications based on image processing - Hussein Ali Hussein Al Naffakh; Rozaida Ghazali; Nidhal Khdhair El Abbadi; Ali Nadhim Razzaq (Institute of Advanced Engineering and Science, 2021)
In computer science, virtual image processing is the use of a digital computer to manipulate digital images through an algorithm for many applications. To begin with a new research topic, the must trend application that gets many requests to develop should know. Therefore, many applications based on human skin and human life are reviewed in this article, such as detection, classification, blocking, cryptography, identification, localization, steganography, segmentation, tracking, and recognition. In this article, the published articles with the topic of human skin-based image processing are investigated. The international publishers, such as Springer, IEEE, arXiv, and Elsevier are selected. The searching is implemented with the duration criteria of 2015-2019. It noted that human skin detection and recognition are the most repetitive articles with 43% and 28.5%, respectively of the total number of the investigated articles. The usage of human skin models is being widely used in the image processing of various applications.